Methanol leaf extract of actinodaphne sesquipedalis (Lauraceae) enhances gastric defense against ethanol-induced ulcer in rats - Omar, H.; Nordin, N.; Hassandarvish, P.; Hajrezaie, M.; Azizan, A.H.S.; Fadaeinasab, M.; Majid, N.A.; Abdulla, Mahmood Ameen; Hashim, N.M.; Ali, Hapipah Mohd (Dove Medical Press, 2017)
Actinodaphne sesquipedalis Hook. F. Var. Glabra (Kochummen), also known as “Medang payung” by the Malay people, belongs to the Lauraceae family. In this study, methanol leaf extract of A. sesquipedalis was investigated for their acute toxicity and gastroprotective effects to reduce ulcers in rat stomachs induced by ethanol. The rats were assigned to one of five groups: normal group (group 1), ulcer group (group 2), control positive drug group (group 3) and two experimental groups treated with 150 mg/kg (group 4) and 300 mg/kg (group 5) of leaf extract. The rats were sacrificed an hour after pretreatment with extracts, and their stomach homogenates and tissues were collected for further evaluation. Macroscopic and histological analyses showed that gastric ulcers in rats pretreated with the extract were significantly reduced to an extent that it allowed leukocytes penetration of the gastric walls compared with the ulcer group. In addition, an ulcer inhibition rate of >70% was detected in rats treated with both doses of A. sesquipedalis extract, showing a notable protection of gastric layer. Severe destruction of gastric mucosa was prevented with a high production of mucus and pH gastric contents in both omeprazole-treated and extract-treated groups. Meanwhile, an increase in glycoprotein uptake was observed in pretreated rats through accumulation of magenta color in Periodic Acid Schiff staining assay. Analysis of gastric homogenate from pretreated rats showed a reduction of malondialdehyde and elevation of nitric oxide, glutathione, prostaglandin E2, superoxide dismutase and protein concentration levels in comparison with group 2. Suppression of apoptosis in gastric tissues by upregulation of Hsp70 protein and downregulation of Bax protein was also observed in rats pretreated with extract. Consistent results of a reduction of gastric ulcer and the protection of gastric wall were obtained for rats pretreated with A. sesquipedalis extract, which showed its prominent gastroprotective potential in rats’ stomach against ethanol-induced ulcer.